Market Proximity, Income, and Home Gardening: Investigating Determinants of Household Food Security for Young Children in Samarinda City - Ginting, Riska Mayang Saputri; Reski, Sepsina; Megasari, Anitatia Ratna; Fikri, Mohammad (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Food insecurity remains a significant public health issue, especially among infants and young children. This study aimed to identify the determinants of food security among 6-23-month-old infants in Mangkupalas, Samarinda, Indonesia. A cross-sectional study was conducted among 137 households with infants aged 6-23 months in Puskesmas Mangkupalas area. The study used consecutive sampling in 3 villages namely tenun, mesjid and mangkupalas. Quantitative data were collected using a structured questionnaire and analyzed using spearman rank correlation test.A total of 73.7% of households locatednear markets were food secure compared to 52.5% of those far from markets, and this distance was statistically associated with household food security(p = 0.019, r = -0.201). Household income showed a significant positive association with food security (p = 0.008, r = 0.226), where 76.7% of households earning ≥3,500,000 IDR/month were food secure compared to only 52.2% among those earning ≤1,500,000 IDR/month. Interestingly, home gardening, which theoretically influences food security, was not found to have a significant association(p = 0.884, r = 0.017).The findings indicate that in urban areas, where food access heavily depends on purchasing power and proximity to food sources, household food security is shaped more by economic stability and market access than by subsistence practices like home gardening. Limited land availability and a narrow variety of cultivated crops may constrain the effectiveness of home gardening in contributing to nutritional adequacy.